2017
DOI: 10.1021/acs.bioconjchem.7b00624
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Transforming Growth Factor Beta to Antigen-Loaded Poly(lactide-co-glycolide) Nanoparticles Enhances Efficiency of Antigen-Specific Tolerance

Abstract: Current strategies for treating autoimmunity involve the administration of broad-acting immunosuppressive agents that impair healthy immunity. Intravenous (i.v.) administration of poly(lactide- co-glycolide) nanoparticles (NPs) containing disease-relevant antigens (Ag-NPs) have demonstrated antigen (Ag)-specific immune tolerance in models of autoimmunity. However, subcutaneous (s.c.) delivery of Ag-NPs has not been effective. This investigation tested the hypothesis that codelivery of the immunomodulatory cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 50 publications
3
60
0
1
Order By: Relevance
“…For example, Cappellano et al showed that simultaneous subcutaneous injection of PLGA nanoparticles loaded with either MOG 35−55 or IL-10 ameliorated the course of EAE ( 241 ). TGF-β, another immunoregulatory molecule, coupled to the surface of PLGA nanaopartlces containing PLP 139−151 peptide were shown to improve the tolerogenic effect of Ag-PLGA nanoparticles ( 242 ). Another example is Maldonaldo et al using PLGA nanoparticles loaded PLP 139−151 together with rapamycin, an inhibitor of the mTOR pathway, and demonstrating that a single dose of these particles injected at the peak of disease were able to protect from relapses ( 243 ).…”
Section: Targeting Immunological Activity Of Myeloid Cellsmentioning
confidence: 99%
“…For example, Cappellano et al showed that simultaneous subcutaneous injection of PLGA nanoparticles loaded with either MOG 35−55 or IL-10 ameliorated the course of EAE ( 241 ). TGF-β, another immunoregulatory molecule, coupled to the surface of PLGA nanaopartlces containing PLP 139−151 peptide were shown to improve the tolerogenic effect of Ag-PLGA nanoparticles ( 242 ). Another example is Maldonaldo et al using PLGA nanoparticles loaded PLP 139−151 together with rapamycin, an inhibitor of the mTOR pathway, and demonstrating that a single dose of these particles injected at the peak of disease were able to protect from relapses ( 243 ).…”
Section: Targeting Immunological Activity Of Myeloid Cellsmentioning
confidence: 99%
“…Leveraging this strategy, a number of recent preclinical studies have demonstrated particulate codelivery of self‐antigens and regulatory signals can effectively promote antigen‐specific tolerance . These studies have been conducted in multiple mouse models of autoimmune disease, and in settings aimed at preventing formation of antidrug antibodies against recombinant protein drugs.…”
Section: Nps and Mps Offer Attractive Features As Carriers Of Signalsmentioning
confidence: 99%
“…To develop a T cell activation by targeted delivery, SD‐208 (TGFβR1 inhibitor) encapsulated in PLGA NPs was demonstrated to restore the function of effector T cells . Moreover, incorporation of TGFβ onto the antigen loaded NPs could enhance the efficacy in lower dosage …”
Section: Negotiators With Biological Barriersmentioning
confidence: 99%